2017
DOI: 10.1007/s12291-017-0633-x
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Gene Expression Profile of Endogenous Antioxidant Enzymes: CAT, MnSOD and GPx in Dengue Patients

Abstract: Dengue is an arthropod-borne threat among tropical countries. Currently no effective means to treat the virus or to predict which patient will develop the severe form of the disease. Recently the relationship between oxidative/antioxidative response and dengue pathogenesis was suggested. Based on this the present study has analysed the expression of endogenous antioxidant genes: Catalase (CAT), Superoxide dismutase (MnSOD) and Glutathione peroxidase in patients with dengue compared to other febrile illness (OF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…PBMCs were separated from whole blood obtained from Healthy controls, OFI and dengue cases using HiSep LSM 1077 (Himedia, Mumbai, India), washed with PBS twice and stored in 1 mL RNAiso Plus reagent (Takara Bio Inc., Shiga, Japan) and kept at − 80° as described in our earlier studies [ 10 ]. Total RNA was extracted using RNA easy minikit (Qiagen, GmbH, Hilden, Germany) based on the manufacturer’s protocol.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…PBMCs were separated from whole blood obtained from Healthy controls, OFI and dengue cases using HiSep LSM 1077 (Himedia, Mumbai, India), washed with PBS twice and stored in 1 mL RNAiso Plus reagent (Takara Bio Inc., Shiga, Japan) and kept at − 80° as described in our earlier studies [ 10 ]. Total RNA was extracted using RNA easy minikit (Qiagen, GmbH, Hilden, Germany) based on the manufacturer’s protocol.…”
Section: Main Textmentioning
confidence: 99%
“…The primers of the endogenous reference genes and target gene were used based on previous studies [ 9 , 10 , 17 , 20 ] and are described in Additional file 1 : Table S1. All reactions were performed in duplicates with a standard run protocol of initial denaturation at 95° for 30 s followed by 40 cycles of denaturation (95° for 5 s) and a combined annealing and extension (60° for 30 s).…”
Section: Main Textmentioning
confidence: 99%
“…Recently, Cherupanakkal, et al (Cherupanakkal et al, 2017), reported that MnSOD gene expression was not associated with severity of dengue disease in children and adults. In addition to the above, we have not found statistically significant differences in MnSOD activity between patients with severe dengue and those with dengue with warning signs, in both adults and children.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the explanations reported by Cherupanakkal, et al (Cherupanakkal et al, 2017), it is necessary to consider the presence of IgM autoantibodies against MnSOD, which could inhibit the protective effects of MnSOD. These antibodies have been reported in patients with acute viral infections (Ritter et al, 1994;Semrau et al, 1998), and it has been shown that may contribute to the oxidative damage of endothelial cells (Dalpke et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, expression levels of endogenous antioxidant genes including catalase (CAT), manganese superoxide dismutase (MnSOD), and glutathione peroxidase (GPX) were found to be downregulated in dengue patients. Of these, significant downregulation of MnSOD expression was recorded in patients with secondary dengue infection [ 126 ]. More results from dengue patients also showed significantly lower levels of the plasma Trolox-equivalent antioxidant capacity, serum paraoxonase, and erythrocyte-reduced glutathione (GSH) and glutathione peroxidase (GPx) activities [ 127 ].…”
Section: First-line Antioxidant Defense In Mosquito Cells With Denmentioning
confidence: 99%